Application of a bottom-up approach to reduce healthcare disparity between the urban and rural areas - Malicka, Agnieszka; George, Namrita (Journal of Medical Science, 2021)
Disparity in access to healthcare between rural and urban regions occurs world-wide, both in higher and lower income countries. To offset poor health outcomes a number of approaches to structuring healthcare services can be used. Several factors have been identified to play a role, however there are differing degrees of severity in how they contribute to the healthcare gap - depending on whether a higher or lower income country is being evaluated. Traditionally, healthcare systems worldwide adopt a top-down approach which is initiated by large institutions providing resources required for large scale projects along with centralisation of efforts. Although it does lead to change, the results can be short-lived. The authors discuss the bottom-up approach used in ASHWINI organisation in Gudalur, India which allowed for the development of accessible and sustainable healthcare system managed by the community. Other projects, based in part on the principles of a bottom-up approach, have been applied in other countries to reduce healthcare disparities. When designed to deliver geographically-accessible, locally managed, culturally appropriate care, the bottom-up approach can provide sustainable results and being universal in nature, it could be applied in other setting with similar set up.
Keywords: Barriers to Healthcare; Rural Healthcare; Antenatal Care; Child Malnutrition; Bottom-up approach; ASHWINI